2021
DOI: 10.1038/s41430-020-00852-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus casei on lipid metabolism and intestinal microflora in patients with alcoholic liver injury

Abstract: Background The present study aims to investigate the effect of Lactobacillus casei on lipid metabolism and intestinal microflora in patients with alcoholic liver injury. Methods In a double-blind randomized controlled trial, 158 recruited alcoholic liver injury patients were randomized to three treatments for 60 days: low-dose group (LP, n = 58, 100 ml of Lactobacillus casei strain Shirota (LcS)), high-dose group (HP, n = 54, 200 ml of LcS), and positive control group (PC, n = 46, 100 ml of special drinks with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 37 publications
2
27
1
1
Order By: Relevance
“…Other randomized-controlled trials of Lactobacillus casei supplements in patients with alcoholic liver injury support this finding. 111 In general, the mechanisms by which probiotics prevent chronic liver injury include: reducing gut-derived microbial LPS by restoring the bowel flora, repairing the intestinal mucosa and barrier function, modulation of the immune system, and reducing inflammatory cytokine levels. 112…”
Section: Probioticsmentioning
confidence: 99%
“…Other randomized-controlled trials of Lactobacillus casei supplements in patients with alcoholic liver injury support this finding. 111 In general, the mechanisms by which probiotics prevent chronic liver injury include: reducing gut-derived microbial LPS by restoring the bowel flora, repairing the intestinal mucosa and barrier function, modulation of the immune system, and reducing inflammatory cytokine levels. 112…”
Section: Probioticsmentioning
confidence: 99%
“…Furthermore, even heat-killed strains and breaking solutions can ameliorate ALD [ 19 , 20 ]. Numerous studies have reported that probiotics can attenuate alcoholic liver damaged mainly via improving lipid metabolism [ 21 ], reducing TNF- α [ 22 ], IL-6 [ 23 ], and IL-1 β [ 24 ], and ameliorating oxidative stress [ 25 ]. Reducing oxidative stress includes reducing MDA levels, increasing SOD activity [ 23 ], and regulating the keep-Nrf2-ARE signaling pathway [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human study, supplementation of patients with alcoholic liver injury with L. casei significantly decreased their serum TG and LDL-C. The amounts of Lactobacillus and Bifidobacterium were increased compared to those in the control group; consequently, gut microbiota disorders were controlled, and lipid metabolism was improved [94]. Many studies have shown that Lactobacillus improves ALD.…”
Section: Alcoholic Liver Diseasementioning
confidence: 95%